2023
DOI: 10.35961/salee.v4i1.533
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Talk and Its Impact on Young Learners’ Interaction in The Learning Environment

Abstract: Teacher talk otherwise opportunities for second language learning. However, teachers are often unaware how their talk influences opportunities for students’ language development in the classroom. This study explores teachers’ talk and its impact on young learners’ interaction in learning environment specifically in Raudhatul Athfal (RA) Muslimat Arif Rahman Jombang. This research using a qualitative design and the data collection techniques from recorded audio-visually; teachers’ talk transcripts; events or occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…finding was significantly similar to what found in Nasir, et al research (2018) where the teacher talk type of giving directions was reached the highest percentage. These findings are supported by Dagarin, in (Cahyani & Chotimah, 2023) who stated that the teachers act as a resource, facilitator, manager, controller, and director. To motivate the students to engage in the instructive and learning activities, the teacher's directions were needed.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…finding was significantly similar to what found in Nasir, et al research (2018) where the teacher talk type of giving directions was reached the highest percentage. These findings are supported by Dagarin, in (Cahyani & Chotimah, 2023) who stated that the teachers act as a resource, facilitator, manager, controller, and director. To motivate the students to engage in the instructive and learning activities, the teacher's directions were needed.…”
Section: Discussionmentioning
confidence: 58%
“…Despite this, some research revealed that teachers in Indonesia heavily regulate and dominate student involvement in English classes (Cahyani & Chotimah, 2023). According to a study by (Maulana et al, 2012) , teachers in Indonesia have limited engagement with the students.…”
Section: Introductionmentioning
confidence: 99%